Does education effect the rates of prophylactic vaccination in elderly diabetics?. (October 2016) - Altay, Mustafa; Ateş, İhsan; Altay, Fatma Aybala; Kaplan, Mustafa; Akça, Ömer; Özkara, Adem
Highlights: Vaccination rates were established to be very low in geriatric group. The reason for this low rates were assessed as educational defects. After being education, vaccination rates increased about 3–9 fold. Abstract: Aims: This study is performed for inspecting vaccination rates in geriatric patients, negatory effects leading to unvaccination and changes occurring in vaccination rates by patient education. Methods: This study is planned in a combination of two formats: retrospectively for determining last 5 years' vaccination rates of patients and prospectively for determining the change in vaccination rates after patient education. Totally 579 diabetic patients, 206 patients of 65 years and over (group 1) and 373 patients under 65 years (group 2) were admitted to the study. Results: Among preeducational reasons of avoiding vaccination, not to need vaccination was more frequently seen in group 2 when compared to group 1 (98.1% vs 91.7%, p  < 0.001). Pneumococ, influenzae and hepatitis vaccination rates all increased after education in the whole study population. (1.4% vs 12.4%, 12.1% vs 36.6%, 0.5% vs 3.8%, respectively; p  < 0.001). Conclusions: It is seen that giving detailed information to geriatric patients about necessary vaccines and removing suspicions and anxiety about vaccination (about adverse events, for example) makes the vaccination rates raise. Primarily health professionals should be educated for this aim and they shouldn't withhold the effort to give sufficient education to patients on time.